Evaluation of the malignancy risk in benign breast disease using screening mammography - Rajamanickam, Bharathidasan; Narayanan, Maheshwari; Dandapani, Mithun Govind; ., Ambujam (International Surgery Journal, 2019)
Background: Breast cancer is the most common female cancer worldwide representing nearly 25% of the population. The study was designed to find the correlation between mammographic screening and histopathology in the diagnosis of malignancy among patients breast disease. Methods: This analytical study was done on 163 patients who came to the General Surgery Out-Patient Department, VMMC, Karaikal were screened. From this, 125 patients who were clinically diagnosed with benign breast disease were further evaluated with mammography. A detailed history, clinical examination, and investigations including mammography, histopathological examination in the operated specimen were done. Results: In the study 10% lump in the central area, 20% in lower inner quadrant, 12% in lower outer quadrant, 22% in upper inner quadrant and 36% in upper outer quadrant. In the study, all the 100 subjects were diagnosed to have a benign lesion in mammogram, in hpe 87% were diagnosed to have benign lesion and 13% were diagnosed to have malignant lesions. Conclusions: Even though BI-RADS 2 and 3 mammography showed the majority of benign lesions, there is an increasing trend of malignancy in higher BI-RADS criteria, on further histopathological examination. Sensitivity, positive predictive value, and diagnostic accuracy are very high for mammographic screening.